Efficient bilateral trade via two-stage mechanisms under one-sided asymmetric information - KUNIMOTO, Takashi (Institutional Knowledge at Singapore Management University, 2021)
This paper considers a bilateral-trade model with one-sided asymmetric information in which one agent (seller) initially owns an indivisible object and is fully informed of its value, while the other agent (buyer) intends to obtain the object whose value is unknown to himself. As Jehiel and Pauzner (2006) show that no mechanisms can generally result in eﬃcient, voluntary bilateral trades, we aim to overturn this impossibility result by employing two-stage mechanisms (Mezzetti (2004)) in which ﬁrst, the outcome (e.g., allocation of the goods) is determined, then the agents observe their own outcome-decision payoﬀs, and ﬁnally, transfers are made. We show that the generalized two-stage Groves mechanism induces eﬃcient, voluntary bilateral trades. On the contrary, we also show by means of an example that the generalized two-stage Groves mechanism fails to achieve eﬃcient, voluntary trades in a two-sided asymmetric information setup in which both parties have private information and each party’s valuation depends on the other’s information in the same way.